FORMATION OF THE STATE ANTI-MONOPOLOGY POLICY IN THE CONDITIONS OF THE DIGITAL ECONOMY DEVELOPMENT - BOLHOV, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the concept of the digital economy and its influence on the formation and development of state antimonopoly policy. Based on the existing approaches to the definition of the concept of the digital economy, an own vision and interpretation of this concept as a set of infrastructural elements, with a high level of digitalization and the development of the on-demand economy, as well as the growth of the volume and variety of information services, the development and implementation of digital innovations, and the wide use of ICT are proposed and platforms in all spheres of society. The specific characteristics of digital markets, which determine the peculiarities of the functioning and development of these markets, are considered. A review of the leading companies operating in digital markets showed that these companies not only occupy a significant part of the national market, but also very often have a significant share of the global consumer market, driven by economies of scale and network effects. In addition, it was determined that developing countries have their own national companies that provide goods and services in the digital sphere based on the specifics of the consumer markets of each individual region and realizing competitive advantages related to logistics and payment methods. Moreover, national companies are often based on the experience of world leaders, may have foreign financing and even be absorbed by global industry leaders to one degree or another. Also determined are the dynamics of the world’s leading companies in the field of digital services, which are positive and demonstrate significant financial results. Antimonopoly policy in the field of digital services is at the initial stage of its formation. Difficulties in the formation of state antimonopoly policy are determined by the peculiarities of digital markets, their variability and dynamic development. It was established that the state should be interested in the development of digital markets, as well as the development of competition in these markets to ensure the competitiveness of national companies in these markets both at the national and international level.